Intraoperative tissue classification methods in orthopedic and neurological surgeries: A systematic review - Massalimova, Aidana; Timmermans, Maikel; Esfandiari, Hooman; Carrillo, Fabio; Laux, Christoph J.; Farshad, Mazda; Denis, Kathleen; Fürnstahl, Philipp (Frontiers in Surgery, 2022)
Accurate tissue differentiation during orthopedic and neurological surgeries is critical, given that such surgeries involve operations on or in the vicinity of vital neurovascular structures and erroneous surgical maneuvers can lead to surgical complications. By now, the number of emerging technologies tackling the problem of intraoperative tissue classification methods is increasing. Therefore, this systematic review paper intends to give a general overview of existing technologies. The review was done based on the PRISMA principle and two databases: PubMed and IEEE Xplore. The screening process resulted in 60 full-text papers. The general characteristics of the methodology from extracted papers included data processing pipeline, machine learning methods if applicable, types of tissues that can be identified with them, phantom used to conduct the experiment, and evaluation results. This paper can be useful in identifying the problems in the current status of the state-of-the-art intraoperative tissue classification methods and designing new enhanced techniques.